Navigating Ethics and Empathy in Disaster Photojournalism in Indonesia - Anis, Elis Zuliati (Universitas Gadjah Mada, 2024)
This study is based on the scholars' critique of the Indonesian media reporting on disaster for focusing on vulnerable groups' suffering, sadness, and grief. The absence of comprehensive journalistic ethical guidelines for disaster published photographs in Indonesia, might contribute to the recurring choice and publication of such images in Indonesian print newspapers. Examining major disasters, including the 2004 Aceh Tsunami, the 2006 Yogyakarta and Central Java earthquake, the 2010 Mt. Merapi Eruption, and the 2015 Sumatra Forest fires, this research provides critical evidence for re-evaluating the Indonesian journalist’s codes of ethics, especially concerning the published photographs of disaster victims. Methodologically, this study draws on interviews with six Indonesian journalists and two media practitioners, exploring the ethical practices and dilemmas in photojournalism with a specific emphasis on disaster reporting in Indonesian print newspapers. The transcripts were analysed thematically, emphasising the repeating ideas or patterns present in the text. It also includes an analysis of three graphic/disturbing photographs from the 2010 Mt Merapi eruption coverage in Kompas and Kedaulatan Rakyat newspapers. The study highlights the complex balance between ensuring truthful reporting and honouring the dignity and privacy of those affected by disasters. It advocates for a nuanced method in disaster coverage that harmonizes journalistic integrity with a compassionate portrayal of victims. This research contributes to the discourse on ethical disaster photojournalism and has significant implications for policy development, journalist training programs, and the revision of journalistic codes of ethics, promoting a more empathetic and responsible approach in the field.